Tingkat Adopsi Inovasi Teknologi Pengusaha Sentra Industri Kecil Kerajinan Gerabah Kasongan Kabupaten Bantul - Sumarno, Muhammad (Jurnal Manajemen dan Kewirausahaan, 2010)
This research is aimed at revealing and understanding: (1) the effect of innovation information intensity, working capital, entrepreneurship, and educational level to the level of technological innovation adoption; (2) the effect of innovation information intensity, amount of working capital, and entrepreneurship, to the level on the innovation production level through technological innovation adoption level; (3) the effect of technological innovation adoption level on the innovation production level. The sampling technique was taken by using Porpusive Random Sampling. The sample size consisted of 45 entrepreneurs, consists of 40 home industry and 5 small scale entrepreneurs. The analysis of data used multiple regression, and path analysis. The interpretation of data analysis results were done at level of significance 5%. The findings of the research shows: (1) independent variables of innovation information intensity, working capital, entrepreneurship, and educational level have a positive impact on the technological innovation adoption level; innovation information intensity had positive impact on the technological innovation adoption level with a coefficient effect=0.50; the working capital had a positive impact=0.35; the entrepreneurship had a positive impact=0,26; and the educational level had a positive correlation on the technological innovation adoption level with r=0.44; (2) the innovation information intensity, working capital, and entrepreneurship have indirectly positive impact (through technological innovation adoption level) on the innovation production level; with coefficient of effects are 0,38; 0,26 and 0,20 respectively. (3) the technological innovation adoption level had a positive impact on the innovation production level with a coefficient of effect=0,75.